Knots in the cath lab, an embarrassing complication of radial angiography. Issue 1 (8th March 2013) - Gupta, Prabha Nini; Praveen, G K; Ahmed, Sajan Z; Kumar, B Krishna; V S, Sajith
Abstract : Most case reports or series describe knots in the venous system such as knots of Swan-Ganz catheters, pacing wires or thermodilution catheters. Knots during radial angiography are relatively rare. Here we describe a simple method of unravelling a radial knot via the femoral route, together with a review of the literature on knots in the catherisation laboratory and the techniques to deal with them.